2017
DOI: 10.1017/s1047951117000841
|View full text |Cite
|
Sign up to set email alerts
|

Key drivers of patient experience in ambulatory paediatric cardiology

Abstract: Patient experience is becoming a central focus of healthcare. A broad range of studies on how to increase patient satisfaction ratings exists; however, they lack the specificity to adequately guide physicians and hospitals on how to improve patient experience. The objective of this study was to define the aspects of patient experience within paediatric cardiologist practices that can serve as predictors of excellent patient satisfaction. From 1 January, 2013 to 28 February, 2015 (26 months), outpatients who vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Considering the positive correlation between the patient experience and clinical outcomes, it needs to be considered as a tool to refine the quality of care and enhance the implementation of the concept of patient-centeredness [ 18 , 64 , 68 ]. In a recent study evaluating key drivers of the patient experience in pediatric population with heart disorders, cheerfulness during practice, the cohesiveness of staff, and explanation of problems and conditions from the providers were identified as predictive of overall satisfaction [ 69 ]. Furthermore, it has also been reported in a study evaluating interview narratives who had been hospitalized that, medication management, physical comfort, and emotional security were what matter most [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the positive correlation between the patient experience and clinical outcomes, it needs to be considered as a tool to refine the quality of care and enhance the implementation of the concept of patient-centeredness [ 18 , 64 , 68 ]. In a recent study evaluating key drivers of the patient experience in pediatric population with heart disorders, cheerfulness during practice, the cohesiveness of staff, and explanation of problems and conditions from the providers were identified as predictive of overall satisfaction [ 69 ]. Furthermore, it has also been reported in a study evaluating interview narratives who had been hospitalized that, medication management, physical comfort, and emotional security were what matter most [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in outpatient pediatric cardiology, a discipline with an acuity and scientific complexity similar to hematologyoncology, demonstrated that teamwork and explanations of problems/conditions were the CG-CAHPS metrics most associated with practice recommendations, metrics that had a comparable impact in our study. 26 In a study of the ambulatory pediatric neurology setting, staff teamwork was also identified as being strongly associated with recommending the practice to others. 27 Our study underscores the importance of both actual and perceived teamwork among physicians, nurses, and other staff members.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 In a retrospective study from 2013 to 2015 involving outpatients of a pediatric cardiology practice, Allam et al determined that a patient's rating of their health care provider's ability to explain problems and conditions in a way that was easy to understand was a key aspect of patient experience and a vital predictor of overall patient satisfaction (P < .001). 40 However, it is important to interpret patient satisfaction data with caution because this metric may be affected by an individual's insight and expectations, mental health status, the physician's prescription habit, and the hospital's reimbursement model. Although it is important for clinicians to personalize patients' experiences to improve patient satisfaction and, ultimately, health outcomes, linking hospital reimbursement with patient satisfaction scores as an incentive to achieve an optimal patient experience carries its own risks.…”
Section: Patient Satisfactionmentioning
confidence: 99%